DISPARITAS PENJATUHAN PIDANA DALAM PERKARA PENCURIAN DENGAN PEMBERATAN DI PENGADILAN NEGERI TAKENGON (Studi Putusan Nomor 79/Pid.B/2022/PN.Tkn, Nomor 33/Pid.B/2022/PN.Tkn dan Nomor 13/Pid.B/2022/PN.Tkn) - Arafah, Arafah - (Program Studi Magister Hukum Universitas Malikussaleh, 2025)
Disparity in criminal sentences is basically a phenomenon that often occurs in criminal law enforcement efforts. Disparity is the application of unequal punishment to the same crime (Same Offence) or to crimes whose dangerous nature can be compared (Offences of Comparable Seriousness) without a clear justification. Disparity in sentencing can be found in many cases, one of which occurred at the Takengon District Court in Decision Number 79/Pid.B/2022/PN.Tkn, Number 33/Pid.B/2022/PN.Tkn and Number 13/Pid.B/2022/PN.Tkn. This research is an empirical legal research with a case approach that examines court decisions. The data sources in this study consist of two forms, namely primary data sources obtained from interviews with respondents and informants. In addition, it also uses secondary data sources which are divided into three legal materials, namely primary legal materials, secondary legal materials, and tertiary legal materials. The data collected was then analyzed using qualitative data analysis techniques. The results of this study found that the occurrence of disparity in sentencing in Decision Number 79/Pid.B/2022/PN.Tkn, Decision Number 33/Pid.B/2022/PN.Tkn and Decision Number 13/Pid.B/2022/PN.Tkn, occurred due to several things including 1) the factor of the judge's freedom in assessing. 2) The factor of differences in aggravating and mitigating circumstances between the three cases. 3) The factor of differences in the consequences caused by the perpetrators in the three cases. The disparity in sentencing in aggravated theft cases, especially in Decision Number 79/Pid.B/2022/PN.Tkn, Decision Number 33/Pid.B/2022/PN.Tkn and Decision Number 13/Pid.B/2022/PN.Tkn is something that is permissible and common. The disparity in these three cases was formed automatically because each case has its own legal facts which are different from each other